The Nile and the Grand Ethiopian Renaissance Dam: Is There a Meeting Point between Nationalism and Hydrosolidarity?. (July 2015) - Abdelhady, Dalia; Aggestam, Karin; Andersson, Dan‐Erik; Beckman, Olof; Berndtsson, Ronny; Palmgren, Karin Broberg; Madani, Kaveh; Ozkirimli, Umut; Persson, Kenneth M.; Pilesjö, Petter
Abstract The soon‐to‐be completed Grand Ethiopian Renaissance Dam (GERD), which will be the largest hydroelectric power plant and among the largest reservoirs in Africa, has highlighted the need for expanding traditional integrated water resources management to better include the cultural, social, and political complexities of large water infrastructure in development projects. The GERD will store a maximum of 74 billion cubic meters of water corresponding to approximately the average annual outflow of the Nile from the Aswan high dam. Undoubtedly, the GERD will be vital for energy production and a key factor for food production, economic development, and poverty reduction in Ethiopia and the Nile Basin. However, the GERD is also a political statement that in one stroke has re‐written the hydropolitical map of the Nile Basin. The GERD has become a symbol of Ethiopian nationalism or "renaissance" (hidase in Amharic). A contrasting concept to nationalism is hydrosolidarity. This concept has been put forward to better stress equitable use of water in international water management challenges that would lead to sustainable socioeconomic development. We use the opposing notions of nationalism and hydrosolidarity at three different scales, everyday politics, state policies, and interstate and global politics to analyse some aspects of the new hydropolitical map of the Nile Basin. We argue that nationalism and national interests are not necessarily negative standpoints but that there may instead be a meeting point where regional and national interests join with hydrosolidarity principles. We believe that this meeting point can maximize not only the common good, but also the good from a national interest point of view. For this, it is important not increase collaboration instead of being locked in to the historical narrative of nationalistic culture and historical discourse. This would benefit and improve future sustainability.